"Moving choice to center stage" in the relationship between the self and offending: Integrating symbolic interactionism and rational choice - O'Neill, Jennifer (European journal of criminology, 2025)
Symbolic interactionism (SI) and rational choice (RC) can inform two parts of one process in which an individual's self guides their choice to offend. Building on the work of others who have referenced their theoretical compatibility, I draw explicit connections between the key concepts of each perspective to propose an integrated framework for examining variation in offending both between- and within-persons. The framework proposes a process by which individuals hold several structured role-identities that inform expectations of the risks, costs, and rewards of offending, and together these role-identities comprise a core self that influences the degree to which one weighs these expectations (preferences) in behavioral decisions. Further development of this integrated model can advance empirical tests of SI and RC.